Changes in Romanian Higher Education After 1990 - Raluca Mariana Drăgoescu (Revista Română de Statistică, 2013)
Education is one of the key factors in the economic development of any country. The higher education system in Romania has undergone major transformations in the last 23 years. This paper introduces the evolution of some indicators characterizing higher education in Romania in the last 23 years. In this period we have witnessed an important increase in the number of students but this increase was not correlated with increased numbers of teachers or endowment development. Extensive development can not be sustained on long-term, which has been shown in the past 3 years when the number of students began to drop. The data presented in this study come from the NIS, UNESCO Institute for Statistics and EUROSTAT. Data processing has been made using econometric methods such as ADF unit root tests and Granger Causality.